Trained immunity: A “new” weapon in the fight against infectious diseases - Dagenais, Amy; Villalba-Guerrero, Carlos; Olivier, Martin (Frontiers in Immunology, 2023)
Innate immune cells can potentiate the response to reinfection through an innate form of immunological memory known as trained immunity. The potential of this fast-acting, nonspecific memory compared to traditional adaptive immunological memory in prophylaxis and therapy has been a topic of great interest in many fields, including infectious diseases. Amidst the rise of antimicrobial resistance and climate change—two major threats to global health—, harnessing the advantages of trained immunity compared to traditional forms of prophylaxis and therapy could be game-changing. Here, we present recent works bridging trained immunity and infectious disease that raise important discoveries, questions, concerns, and novel avenues for the modulation of trained immunity in practice. By exploring the progress in bacterial, viral, fungal, and parasitic diseases, we equally highlight future directions with a focus on particularly problematic and/or understudied pathogens.